2004
DOI: 10.1128/aem.70.4.2404-2413.2004
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Marine Crenarchaeota Group I in the Vicinity of Deep-Sea Hydrothermal Systems

Abstract: Distribution profiles of marine crenarchaeota group I in the vicinity of deep-sea hydrothermal systems were mapped with culture-independent molecular techniques. Planktonic samples were obtained from the waters surrounding two geographically and geologically distinct hydrothermal systems, and the abundance of marine crenarchaeota group I was examined by 16S ribosomal DNA clone analysis, quantitative PCR, and whole-cell fluorescence in situ hybridization. A much higher proportion of marine crenarchaeota group I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 60 publications
5
85
0
Order By: Relevance
“…Several studies have reported the SUP05 group of sulfur-oxidizing Gammaproteobacteria in deep-sea hydrothermal plumes in widespread geographical locations (Sunamura et al, 2004;Dick and Tebo, 2010;German et al, 2010). Other prevalent microbial groups identified in plumes include Epsilonproteobacteria (Sunamura et al, 2004;Nakagawa et al, 2005;German et al, 2010), ammonia-oxidizing Betaproteobacteria (Lam et al, 2008), methanotrophs (Naganuma et al, 2004;Lam et al, 2008) and Marine Group I (MGI) archaea (Takai et al, 2004). Although these studies have expanded our knowledge of the major microbial groups present in plumes, it remains unclear which microbes are metabolically active in the plume environment, how they are linked to biogeochemical processes of interest and whether they are derived from seafloor environments (for example, chimneys and sediments) or ambient deep seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the SUP05 group of sulfur-oxidizing Gammaproteobacteria in deep-sea hydrothermal plumes in widespread geographical locations (Sunamura et al, 2004;Dick and Tebo, 2010;German et al, 2010). Other prevalent microbial groups identified in plumes include Epsilonproteobacteria (Sunamura et al, 2004;Nakagawa et al, 2005;German et al, 2010), ammonia-oxidizing Betaproteobacteria (Lam et al, 2008), methanotrophs (Naganuma et al, 2004;Lam et al, 2008) and Marine Group I (MGI) archaea (Takai et al, 2004). Although these studies have expanded our knowledge of the major microbial groups present in plumes, it remains unclear which microbes are metabolically active in the plume environment, how they are linked to biogeochemical processes of interest and whether they are derived from seafloor environments (for example, chimneys and sediments) or ambient deep seawater.…”
Section: Introductionmentioning
confidence: 99%
“…These hydrothermal inputs contribute to ammonium concentrations of up to 3 mM in GB deep waters (1800-2000 m depth; Lam, 2004). Gene-based surveys have shown that the MGI dominate the GB plume archaeal community Tebo, 2010, Lesniewski et al, 2012), and that MGI are more abundant in plumes than background seawater in the deep Indian Ocean and Okinawa Trough (Takai et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the microbial communities that are closely associated with the high-temperature hydrothermal fluid emissions of the Kairei field, the planktonic microbial communities found in the hydrothermal plumes and habitats in the vicinity of this field were not significantly different from those observed in other deep-sea hydrothermal environments (Takai et al 2004b). Based on examination of the relative abundance of Marine Group I (Creanarchaeota and Epsilonproteobacteria) populations in the planktonic microbial communities of the hydrothermal plumes, the communities in the Kairei field showed much less abundant Epsilonproteobacteria populations compared to the Iheya North field of the Okinawa Trough.…”
Section: Microbial Communities and Microorganisms Isolated From The Cmentioning
confidence: 60%
“…Based on examination of the relative abundance of Marine Group I (Creanarchaeota and Epsilonproteobacteria) populations in the planktonic microbial communities of the hydrothermal plumes, the communities in the Kairei field showed much less abundant Epsilonproteobacteria populations compared to the Iheya North field of the Okinawa Trough. However, microbial populations other than Marine Group I, such as the SUP05 group Gammaproteobacteria, a cosmopolitan microbial population that dominates hydrothermal plume communities (Sunamura et al 2004;Dick and Tebo 2010), were not quantitatively estimated (Takai et al 2004b). In addition, La Duc et al (et al 2007) reported that many of the heterotrophic bacteria isolated from the Kairei hydrothermal plumes displayed high multi-stressor tolerance to desiccation, peroxide exposure, and UV and gamma ray irradiation.…”
Section: Microbial Communities and Microorganisms Isolated From The Cmentioning
confidence: 99%